Battery electric vehicle usage pattern analysis driven by massive real-world data. (1st July 2022) - Cui, Dingsong; Wang, Zhenpo; Liu, Peng; Wang, Shuo; Zhang, Zhaosheng; Dorrell, David G.; Li, Xiaohui
Abstract: Electric vehicles (EVs) are playing a key role in supporting transportation electrification and reducing air pollution and greenhouse gas emissions. The increased number of EVs may also bring about some issues concerning energy system structure optimization and efficiency enhancement. User behavior analysis and simulation is an important method to solve these issues. A stochastic model for describing the usage of vehicle is essential to handle simulation models and behavior models. Therefore, a more comprehensive understanding of EV usage patterns is necessary for the model establishment. The paper focuses on the 2, 047, 222 charging events and 8, 382, 032 travel events collected from 26, 606 battery electric vehicles operating in Beijing, China, in 2018, based on the open lab of National Big Data Alliance of New Energy Vehicles. With the large-scale data resource rather than limited samples, we provide some robust statistical results and some multi-dimensional comparative analysis in the paper, which can be applied in large-scale deployment environments and large population cities. The results can also provide information for charging infrastructures construction, gird management, vehicle charging scheduling, and so forth in Beijing and even other metropolises with similar situations. Highlights: Operational data of 26, 606 battery electric vehicles in Beijing are collected. The usage pattern including charging pattern and travel pattern is investigated. Probability density function is used to analyze usage pattern characteristics. The characteristics of vehicles in different application scenarios are compared.